Influence of Green Knowledge and Green Attitude on Purchase Decisions of BPA-Free Labeled Baby Plastic Products Mediated by Green Trust: A Sustainable Approach: English - Sihombing, Fery Andreas; Widayati, Catur (Dinasti International Journal of Management Science, 2025)
With a focus on the roles of green knowledge, green attitude, and green trust—the latter of which acts as a mediating element within the context of sustainable marketing—this study investigates the factors affecting decisions to buy BPA-free baby plastic products. Despite being necessary for modern living, plastic presents serious health and environmental hazards, especially because of dangerous compounds like bisphenol A (BPA). 185 women in the Jabodetabek region who bought BPA-free baby plastic products participated in the study's survey. A Likert scale and Structural Equation Modelling-Partial Least Square (SEM-PLS) were employed to examine the data. The findings indicate that while green knowledge does not directly affect purchase decisions, green attitude and green trust do have an advantageous and significant impact. Furthermore, the association between green knowledge and purchasing decisions is totally mediated by green trust, while the relationship between green attitude and purchasing decisions is somewhat mediated by green trust. These findings highlight the need of building customer trust through educational programs that highlight the advantages and characteristics of eco-friendly products, offering insightful information for long-term marketing plans.